Assessment of Storm Surge History as Recorded by Driftwood in the Mackenzie Delta and Tuktoyaktuk Coastlands, Arctic Canada - MacLeod, Roger F.; Dallimore, Scott R. (Frontiers in Earth Science, 2021)
The southern Beaufort Sea coastline in Canada experiences significant storm surge events that are thought to play an important role in coastal erosion and influence permafrost dynamics. Unfortunately, many of these events have not been documented with tide gauge records. In this paper, we evaluate coastal driftwood piles as a proxy for estimating maximum storm surge heights and the history of these events. We use historical air photos and data derived from Unoccupied Aerial Vehicle (UAV) imagery to resurvey four coastal stranded driftwood study sites that were first appraised in 1985-86 and add two new regional sites in the Mackenzie Delta. Maximum storm surge heights are similar to observations carried out in the 1980s, however, we refine the elevations with more accuracy and reference these to a vertical datum appropriate for incorporating into sea level hazard assessments. Detailed mapping, historical air photo comparisons and the UAV acquired imagery at a site close to Tuktoyaktuk (3 km away) demonstrate that the highest storm surge at this site (1.98 m CGVD2013) occurred in association with a severe storm in 1970. This event simply shifted driftwood and floated material slightly upslope from an older event that reached 1.85 m (CGVD2013) elevation. The quality and accuracy of the high-resolution Digital Surface Model (DSM) and orthophoto derived from Structure from Motion (SfM) processing of the UAV photographs allowed mapping of four distinct stratigraphic units within the driftwood piles. Based on variations in anthropogenic debris composition, weathering characteristics and history of movement on aerial photographs, we conclude that no storm surge events at Tuktoyaktuk have exceeded ~1.3 m since 1970. While there has been some speculation that ongoing climate change may lead to more frequent large magnitude storm surges in the Beaufort Sea, our study and available tide gauge measurements, suggest that while moderate elevation storm surges may be more frequent in the past several decades they have not approached the magnitude of the 1970 event.